GERAK CEPAT MAHASISWA MBKM DALAM MENCIPTAKAN EDUKASI KEMERGELAPAN PAJAK INDONESIA MELALUI RENJANI DI KPP PRATAMA BANGKALAN - Fainsanu Faraka; Emi Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Tax evasion Indonesia remains a significant challenge within Indonesia's taxation system, directly impacting the nation's revenue. Through the Merdeka Belajar Kampus Merdeka (MBKM) program, students are given the opportunity to contribute as tax volunteers in efforts to enhance taxpayer awareness and compliance. This article examines the active role of MBKM students during their four-month industrial internship at the Pratama Tax Office (KPP) in Bangkalan. Activities included assistance with Annual Tax Return (SPT) filing, taxpayer education, and both online and manual data entry and reporting. The results indicate that student involvement provides effective education, improves tax literacy, and strengthens the connection between tax authorities and the public. These findings underscore the importance of synergy among educational institutions, tax authorities, and society in establishing a transparent and efficient taxation system. The MBKM internship program has proven to not only provide practical experience for students but also contribute directly to combating tax evasion in Indonesia.